ANALISIS MEDAN LISTRIK PADA PLASMA KORONA DENGAN KONFIGURASI CINCIN BIDANG - Wardaya, Asep Yoyo; Nur, Muhammad (BERKALA FISIKA, 2010)
It has been studied efectivity of the electric field and density of current that have been determined by the physical criteria from a long size of cylinder and a radius of thin ring from the corona plasma generator with the plane ring electrode. The result of the calculation is indicate that the strong electrics field will be resulted by the configurations of the thin ring form, contiguity apart between the thin rings (minimum cylinder length) and the size of the thin ring radius which near of the size of external cylinder radius. The radial symmetrical of geometric form of the thin ring is causing it has not current density form at tip of the thin ring. Â  Key words : Plasma,Â  plane-ring, electric field, density of current.